Anti-ultraviolet coating for glass surface and preparation method of anti-ultraviolet coating

By adding composite additives and other modified components in the preparation process of glass surface coating, the problem of aging and dirt adhesion of glass surface coating in the sun is solved, and good anti-ultraviolet, anti-fouling and high adhesion effects are achieved, extending the service life of the glass and reducing maintenance costs.

CN119842280AActive Publication Date: 2025-04-18TENGZHOU YUCHENG GLASS CO LTD
View PDF 4 Cites 0 Cited by

Patent Information

Application Number
CN202510071941.2
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2025-01-16
Publication Date
2025-04-18
Estimated Expiration
2045-01-16

AI Technical Summary

Technical Problem

When existing glass surface coatings are exposed to sunlight for a long time, they are prone to fading, peeling or cracking due to ultraviolet aging, and are prone to adhesion of dust and dirt, reducing light transmittance, and affecting the service life and beauty of the glass.

Method used

An ultraviolet anti-violet coating for glass surface is used. The preparation method includes mechanical stirring of raw materials such as methyl methacrylate, butyl acrylate, acrylic acid, hydroxyethyl acrylate and composite additives, and then adding initiator and heating for polymerization. Finally, talc powder, sodium hexametaphosphate, polyethyl acrylate, polydimethylsiloxane and water for stirring to make the coating.

Benefits of technology

The coating has good antibacterial properties, antifouling properties and high adhesion, which can effectively prevent ultraviolet aging, extend the service life of the glass, reduce maintenance costs, and maintain the light transmittance and aesthetics of the glass.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119842280A_ABST
    Figure CN119842280A_ABST
Patent Text Reader

Abstract

The invention relates to the technical field of coatings, and discloses an anti-ultraviolet coating for a glass surface and a preparation method thereof, the coating comprises the following raw materials: methyl methacrylate, butyl acrylate, acrylic acid, hydroxyethyl acrylate, a composite additive, an initiator, talcum powder, sodium hexametaphosphate, propylene glycol monomethyl ether, poly (ethyl acrylate), polydimethylsiloxane and water; wherein the composite additive is titanium dioxide of which the surface is modified with an antifouling modification component, an alkenyl functional group in the structure of the titanium dioxide can generate cross-linking polymerization with a matrix, the adhesive force and the antifouling property of the coating are effectively improved, and the titanium dioxide can absorb, scatter and reflect ultraviolet light, so that the coating is endowed with good ultraviolet resistance; the structure contains a large number of silicon-oxygen bonds, fluorocarbon bonds and long alkyl chains, so that the antifouling property of the coating is further improved.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to the technical field of coatings, and in particular to an anti-ultraviolet coating for glass surface and a preparation method thereof. Background Art

[0002] As people's requirements for decoration increase, more and more glass products are coated with protective and decorative coatings on their surfaces to improve their performance and appearance. At present, coatings are mainly divided into three types, namely acrylic, epoxy resin and polyurethane. Among them, acrylic coatings have excellent properties, such as good weather resistance, color retention and chemical resistance. These special properties make them widely used in the field of glass products to decorate the appearance of glass while having a good protective effect.

[0003] With the continuous improvement of social and economic levels and the rapid development of science and technology, higher requirements are placed on the functionality of coatings. Compared with ordinary coatings, coatings used for glass surfaces need to have good UV protection. For example, photovoltaic glass, architectural glass, automotive glass, etc. are exposed to sunlight for a long time, and ultraviolet rays will accelerate the aging process of the glass surface coating, causing the coating to fade, peel or crack, thereby affecting the appearance and service life. In addition, dust, dirt and other impurities in the air are easily attached to the surface of the glass, which significantly reduces the light transmittance of the glass and affects the use of the glass. Therefore, the coating used for the glass surface should have good anti-fouling properties to enable the glass to maintain good light transmittance for a long time, thereby extending the service life of the glass and reducing maintenance costs.

[0004] In the prior art, the basic formula is often optimized to improve the performance of coatings. For example, the invention patent with the announcement number CN111171662B discloses a roof waterproof coating and its preparation method. The invention uses a special modified graphene dispersion to modify the polymer emulsion, and the surface of the emulsion is modified by chemical reaction to improve its tensile strength and elongation, and reduce the water absorption of the product. At the same time, the UV resistance is improved, and the mechanical retention rate after UV aging for more than 1500h is more than 90%. The internal cross-linking technology of adding allyl siloxane and the introduction of phosphate esters improve the adhesion and water resistance of the coating. The post-cross-linking technology is introduced by the use of coupling agents to further improve the waterproofness and high temperature stability of the film. Therefore, high-performance coatings can be prepared by adding optimized components in a targeted manner during the preparation of the coating. Summary of the invention

[0005] In order to solve the problems mentioned in the background technology, the purpose of the present invention is to provide an anti-ultraviolet coating for glass surface and a preparation method thereof.

[0006] The purpose of the present invention can be achieved through the following technical solutions:

[0007] A method for preparing an anti-ultraviolet coating for a glass surface, the coating comprising the following raw materials in parts by weight: 30 to 40 parts of methyl methacrylate, 20 to 30 parts of butyl acrylate, 10 to 20 parts of acrylic acid, 5 to 10 parts of hydroxyethyl acrylate, 4 to 8 parts of composite additives, 0.5 to 1.5 parts of initiator, 8 to 10 parts of talc, 1 to 3 parts of sodium hexametaphosphate, 1 to 2 parts of propylene glycol methyl ether, 1 to 3 parts of polyethyl acrylate, 2 to 4 parts of polydimethylsiloxane, and 40 to 60 parts of water;

[0008] The preparation method comprises the following steps:

[0009] (1) adding methyl methacrylate, butyl acrylate, acrylic acid, hydroxyethyl acrylate and composite additives into a reaction kettle, and mechanically stirring to obtain a premix;

[0010] (2) adding an initiator to the premix, mixing well, raising the system temperature to 70-90° C., and keeping the temperature for 4-6 hours to obtain a polymer emulsion;

[0011] (3) adding the polymer emulsion obtained in step (2), talcum powder, sodium hexametaphosphate, propylene glycol methyl ether, polyethyl acrylate, polydimethylsiloxane and water into a stirring kettle, stirring at a stirring rate of 600 to 1000 r / min for 1 to 3 hours, standing to defoam, and obtaining a coating.

[0012] Furthermore, the preparation method of the composite additive comprises the following steps:

[0013] S1: ultrasonically dispersing titanium dioxide in dimethyl sulfoxide to form a dispersion, adding itaconic acid and an esterification catalyst to the dispersion, raising the system temperature to 100-110°C under stirring, keeping the temperature for 5-9 hours, allowing the material to cool naturally, separating the solid material by centrifugation, washing the solid material, and vacuum drying to obtain modified titanium dioxide;

[0014] S2: Add modified titanium dioxide to N,N-dimethylformamide, ultrasonically disperse for 20 to 40 minutes, then add antifouling modification components and p-toluenesulfonic acid, raise the system temperature to 100 to 110°C, keep stirring for 6 to 10 hours, filter and separate the solid material, wash and dry it, and obtain a composite additive.

[0015] Furthermore, in step S1, the average particle size of the titanium dioxide is 5 μm.

[0016] Furthermore, in step S1, the esterification catalyst is any one of p-toluenesulfonic acid, aminosulfonic acid or trifluoromethanesulfonic acid.

[0017] Furthermore, in step S1, the mass ratio of titanium dioxide to itaconic acid is 1:0.1-0.3.

[0018] Technical principle: In the composite additive, firstly, the hydroxyl groups on the surface of titanium dioxide can react with the carboxyl groups in the itaconic acid structure under the action of an esterification catalyst, thereby introducing carboxyl groups and unsaturated olefinic functional groups on the surface of titanium dioxide to obtain modified titanium dioxide; secondly, under the action of p-toluenesulfonic acid, the carboxyl groups on the surface of modified titanium dioxide can further react with the hydroxyl groups in the anti-fouling modified component structure to obtain a composite additive.

[0019] Furthermore, the preparation method of the antifouling modified component comprises the following steps:

[0020] The terminal hydroxyl fluorinated polysiloxane is mixed with dimethyl sulfoxide, stirred to form a uniform solution, and then the epoxy soybean oil and the phase transfer catalyst are added to the solution. After the addition is completed, the temperature is increased to 70-80°C, stirred at this temperature for 4-8 hours, and the solvent is removed by reduced pressure distillation to obtain an antifouling modified component.

[0021] Furthermore, the phase transfer catalyst is boron trifluoride ether complex.

[0022] Furthermore, the mass ratio of the terminal hydroxyl fluorinated polysiloxane to the epoxy soybean oil is 1:0.2-0.4.

[0023] Furthermore, the initiator is any one of azobisisobutyronitrile, azobiscyclohexylmethane or azobisisovaleronitrile.

[0024] Technical principle: In the antifouling modified component, under the action of a phase transfer catalyst, the hydroxyl group in the terminal hydroxyl fluorinated polysiloxane structure can react with the epoxy group in the epoxy soybean oil structure to obtain an antifouling modified component containing a hydroxyl group in the structure.

[0025] An anti-ultraviolet coating for glass surface is prepared by adopting the preparation method.

[0026] Beneficial effects of the present invention:

[0027] (1) The present invention adds a composite additive during the preparation process of the coating, and the raw materials cooperate with each other, so that the prepared coating has good antibacterial properties, antifouling properties and high adhesion, which is beneficial to extending the service life of the coating and reducing maintenance costs.

[0028] (2) The composite additive prepared by the present invention is titanium dioxide with a surface-modified antifouling modified component. After surface modification, the bonding force between the composite additive and the matrix material is greatly enhanced, which helps to evenly and stably disperse the composite additive in the matrix material. In addition, the unsaturated olefinic functional group in the structure of the composite additive can undergo cross-linking polymerization with polymerizable monomers such as methyl methacrylate under the action of an initiator, thereby increasing the cross-linking density and making the interface bonding tighter, thereby effectively improving the adhesion and antifouling performance of the coating. On the one hand, titanium dioxide can absorb, scatter and reflect ultraviolet light, and is an effective ultraviolet shielding agent, which can give the coating good anti-ultraviolet performance and reduce the problems of aging, fading, peeling or cracking of the coating caused by ultraviolet radiation. On the other hand, the composite additive contains a large amount of silicon-oxygen bonds, carbon-fluorine bonds and long alkyl chains, so that the coating surface has a very low surface energy, so that the liquid and the coating surface are not wetted, and impurities such as dust and dirt in the air are difficult to adhere to the coating surface, thereby achieving the purpose of antifouling, avoiding the coating on the glass surface from affecting the visual experience due to dirt accumulation, reducing the number of cleaning times and maintenance costs of the glass, and effectively extending the service life of the glass.

[0029] Of course, any product implementing the present invention does not necessarily need to achieve all of the advantages described above at the same time. BRIEF DESCRIPTION OF THE DRAWINGS

[0030] In order to more clearly illustrate the technical solutions of the embodiments of the present invention, the accompanying drawings required for describing the embodiments will be briefly introduced below. Obviously, the accompanying drawings described below are only some embodiments of the present invention. For ordinary technicians in this field, other accompanying drawings can be obtained based on these accompanying drawings without paying creative work.

[0031] Figure 1 This is an infrared spectrum test chart of the modified titanium dioxide and composite additives prepared in Example 1 of the present invention.

[0032] Figure 2 This is an infrared spectrum test chart of the antifouling modified component prepared in Example 1 of the present invention. DETAILED DESCRIPTION

[0033] The following will be combined with the drawings in the embodiments of the present invention to clearly and completely describe the technical solutions in the embodiments of the present invention. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.

[0034] Example 1. 1. Preparation of composite additives

[0035] S1: 5 g of titanium dioxide with an average particle size of 5 μm was ultrasonically dispersed in dimethyl sulfoxide to form a dispersion, 1.2 g of itaconic acid and 0.05 g of p-toluenesulfonic acid were added to the dispersion, and after the addition, the system temperature was raised to 105° C. under stirring conditions, and the temperature was kept for 7 hours. The material was cooled naturally, and the solid material was separated by centrifugation. The solid material was washed and vacuum dried to obtain modified titanium dioxide;

[0036] S2: Add 5 g of modified titanium dioxide to N,N-dimethylformamide, ultrasonically disperse for 30 minutes, then add 2.6 g of antifouling modification component and 0.1 g of p-toluenesulfonic acid, raise the system temperature to 105°C, keep stirring for 8 hours, filter and separate the solid material, wash and dry it to obtain a composite additive.

[0037] The modified titanium dioxide and composite additives were analyzed by infrared spectroscopy using AVATAR-360 Fourier transform infrared spectrometer. Figure 1 As shown by Figure 1 It can be seen that in the infrared spectrum of modified titanium dioxide, 1755cm -1 The absorption peak of the ester group C=O appears at 1741 cm -1 The absorption peak of carboxyl group C=O appears at 1030cm -1 The absorption peak of the carbon-hydrogen bond in the carbon-carbon double bond appears at 1760cm -1 The absorption peak of the ester group C=O appears at 1030cm -1 The absorption peak of Si-O appears at 1061cm -1 The absorption peak of ether bond COC appears at 3045 cm -1 The absorption peak of the carbon-hydrogen bond in the carbon-carbon double bond appears at .

[0038] 2. Preparation of antifouling modified components

[0039] 5 g of terminal hydroxyl fluorinated polysiloxane was mixed with dimethyl sulfoxide and stirred to form a uniform solution. Then, 1.8 g of epoxy soybean oil and 0.1 g of boron trifluoride ether complex were added to the solution. After the addition was completed, the temperature was raised to 75°C and stirred for 6 hours at this temperature. The solvent was removed by distillation under reduced pressure to obtain an antifouling modified component.

[0040] The antifouling modified components were analyzed by infrared spectroscopy using AVATAR-360 Fourier transform infrared spectrometer. Figure 2 As shown by Figure 2 It can be seen that in the infrared spectrum of the antifouling modified component, 1016cm -1 The absorption peak of Si-O appears at 1263 cm -1The absorption peak of Si-C appears at 1750cm -1 The absorption peak of the ester group C=O appears at 1053 cm -1 The absorption peak of ether bond COC appears at 3310 cm -1 The absorption peak of hydroxyl group OH appears at

[0041] 3. Preparation of coating

[0042] (1) adding 30 g of methyl methacrylate, 20 g of butyl acrylate, 10 g of acrylic acid, 5 g of hydroxyethyl acrylate and 4 g of a composite additive into a reaction kettle, and mechanically stirring the mixture to obtain a premix;

[0043] (2) adding 0.5 g of azobisisobutyronitrile to the premix, mixing well, raising the system temperature to 70° C., and keeping the temperature for 4 h to obtain a polymer emulsion;

[0044] (3) The polymer emulsion obtained in step (2), 8 g of talc, 1 g of sodium hexametaphosphate, 1 g of propylene glycol methyl ether, 1 g of polyethyl acrylate, 2 g of polydimethylsiloxane and 40 g of water were added to a stirring tank, stirred at a stirring rate of 600 r / min for 1 h, and allowed to stand for defoaming to obtain a coating.

[0045] Example 2. Preparation of coating

[0046] (1) adding 35 g of methyl methacrylate, 25 g of butyl acrylate, 15 g of acrylic acid, 8 g of hydroxyethyl acrylate and 7 g of a composite additive into a reaction kettle, and mechanically stirring the mixture to obtain a premix;

[0047] (2) adding 1 g of azobisisobutyronitrile to the premix, mixing well, raising the system temperature to 80° C. and keeping the temperature for 5 h to obtain a polymer emulsion;

[0048] (3) The polymer emulsion obtained in step (2), 9 g of talc, 2 g of sodium hexametaphosphate, 1.5 g of propylene glycol methyl ether, 2 g of polyethyl acrylate, 3 g of polydimethylsiloxane and 50 g of water were added to a stirring tank, stirred at a stirring rate of 800 r / min for 2 h, and allowed to stand for defoaming to obtain a coating.

[0049] The preparation method of the composite additive is the same as that in Example 1.

[0050] Example 3. Preparation of coating

[0051] (1) adding 40 g of methyl methacrylate, 30 g of butyl acrylate, 20 g of acrylic acid, 10 g of hydroxyethyl acrylate and 8 g of composite additives into a reaction kettle, and mechanically stirring to obtain a premix;

[0052] (2) adding 1.5 g of azobisisobutyronitrile to the premix, mixing well, raising the system temperature to 90° C. and keeping the temperature for 6 h to obtain a polymer emulsion;

[0053] (3) The polymer emulsion obtained in step (2), 10 g of talc, 3 g of sodium hexametaphosphate, 2 g of propylene glycol methyl ether, 3 g of polyethyl acrylate, 4 g of polydimethylsiloxane and 60 g of water were added to a stirring tank, stirred at a stirring rate of 1000 r / min for 3 h, and allowed to stand for defoaming to obtain a coating.

[0054] The preparation method of the composite additive is the same as that in Example 1.

[0055] Comparative Example 1. Preparation of coating

[0056] (1) Add 35 g of methyl methacrylate, 25 g of butyl acrylate, 15 g of acrylic acid and 8 g of hydroxyethyl acrylate into a reaction kettle and stir mechanically to obtain a premix;

[0057] (2) adding 1 g of azobisisobutyronitrile to the premix, mixing well, raising the system temperature to 80° C., and keeping the temperature for 5 h to obtain a polymer emulsion;

[0058] (3) The polymer emulsion obtained in step (2), 7 g of titanium dioxide with an average particle size of 5 μm, 9 g of talc, 2 g of sodium hexametaphosphate, 1.5 g of propylene glycol methyl ether, 2 g of polyethyl acrylate, 3 g of polydimethylsiloxane and 50 g of water were added to a stirring tank, stirred at a stirring rate of 800 r / min for 2 h, and allowed to stand for defoaming to obtain a coating.

[0059] Comparative Example 2. Preparation of coating

[0060] (1) Add 35 g of methyl methacrylate, 25 g of butyl acrylate, 15 g of acrylic acid, 8 g of hydroxyethyl acrylate and 7 g of antifouling modification component into a reaction kettle, and stir mechanically to obtain a premix;

[0061] (2) adding 1 g of azobisisobutyronitrile to the premix, mixing well, raising the system temperature to 80° C., and keeping the temperature for 5 h to obtain a polymer emulsion;

[0062] (3) The polymer emulsion obtained in step (2), 9 g of talc, 2 g of sodium hexametaphosphate, 1.5 g of propylene glycol methyl ether, 2 g of polyethyl acrylate, 3 g of polydimethylsiloxane and 50 g of water were added to a stirring tank, stirred at a stirring rate of 800 r / min for 2 h, and allowed to stand for defoaming to obtain a coating.

[0063] The preparation method of the antifouling modified component is the same as that in Example 1.

[0064] Comparative Example 3. Preparation of coating

[0065] (1) Add 35 g of methyl methacrylate, 25 g of butyl acrylate, 15 g of acrylic acid and 8 g of hydroxyethyl acrylate into a reaction kettle and stir mechanically to obtain a premix;

[0066] (2) adding 1 g of azobisisobutyronitrile to the premix, mixing well, raising the system temperature to 80° C. and keeping the temperature for 5 h to obtain a polymer emulsion;

[0067] (3) The polymer emulsion obtained in step (2), 9 g of talc, 2 g of sodium hexametaphosphate, 1.5 g of propylene glycol methyl ether, 2 g of polyethyl acrylate, 3 g of polydimethylsiloxane and 50 g of water were added to a stirring tank, stirred at a stirring rate of 800 r / min for 2 h, and allowed to stand for defoaming to obtain a coating.

[0068] Performance testing:

[0069] The coatings prepared in Examples 1 to 3 of the present invention and Comparative Examples 1 to 3 were evenly coated on the clean tinplate surface after sandblasting to prepare samples that met the specifications. After being thoroughly dried, the performance test was performed on the samples. The adhesion test was performed on the samples according to GB / T 5210-2006 "Adhesion Test for Paints and Varnishes by Pull-off Method"; the samples were placed under an ultraviolet wavelength of 313 nm and an irradiance of 0.54 W / m 2 The UV aging box was used to observe the time when the sample turned yellow to judge the UV resistance of the sample; the PZ-200SD contact angle tester was used to test the water contact angle of the sample to judge the anti-fouling performance of the sample. The specific test results are shown in Table 1:

[0070] Table 1 - Performance Test

[0071] Adhesion(MPa) Yellowing time (h) Water contact angle (°) Example 1 12 >240 150 Example 2 13 >240 152 Example 3 12 >240 151 Comparative Example 1 4 <150 105 Comparative Example 2 5 <48 140 Comparative Example 3 4 <48 104

[0072] From the test results in Table 1, it can be seen that the samples prepared in Examples 1 to 3 have good anti-ultraviolet performance, anti-fouling performance and high adhesion; in the sample prepared in Comparative Example 1, titanium dioxide is used to replace the composite additive. Since it cannot cross-link with the matrix, the anti-fouling performance and adhesion of the sample are poor, and the titanium dioxide that has not been organically modified may agglomerate in the matrix, resulting in a decrease in the anti-ultraviolet performance of the sample; in the sample prepared in Comparative Example 2, an anti-fouling modified component is used to replace the composite additive. Since it cannot cross-link with the matrix, the anti-ultraviolet performance, anti-fouling performance and adhesion of the sample are not as good as those of the embodiment; in the sample prepared in Comparative Example 3, no composite additive is added, so the various properties of the sample are poor.

[0073] The above contents are merely examples and explanations of the concept of the present invention. The technicians in this technical field may make various modifications or additions to the specific embodiments described or replace them in a similar manner. As long as they do not deviate from the concept of the invention or exceed the scope defined by the claims, they should all fall within the protection scope of the present invention.

Claims

1. A method for preparing an anti-ultraviolet coating for a glass surface, characterized in that: The coating comprises the following raw materials in parts by weight: 30 to 40 parts of methyl methacrylate, 20 to 30 parts of butyl acrylate, 10 to 20 parts of acrylic acid, 5 to 10 parts of hydroxyethyl acrylate, 4 to 8 parts of composite additives, 0.5 to 1.5 parts of initiator, 8 to 10 parts of talc, 1 to 3 parts of sodium hexametaphosphate, 1 to 2 parts of propylene glycol methyl ether, 1 to 3 parts of polyethyl acrylate, 2 to 4 parts of polydimethylsiloxane, and 40 to 60 parts of water; The preparation method comprises the following steps: (1) adding methyl methacrylate, butyl acrylate, acrylic acid, hydroxyethyl acrylate and composite additives into a reaction kettle, and mechanically stirring to obtain a premix; (2) adding an initiator to the premix, mixing well, raising the system temperature to 70-90° C., and keeping the temperature for 4-6 hours to obtain a polymer emulsion; (3) adding the polymer emulsion obtained in step (2), talcum powder, sodium hexametaphosphate, propylene glycol methyl ether, polyethyl acrylate, polydimethylsiloxane and water into a stirring kettle, stirring at a stirring rate of 600 to 1000 r / min for 1 to 3 hours, standing to defoam, and obtaining a coating.

2. The method for preparing an anti-ultraviolet coating for glass surface according to claim 1, characterized in that: The preparation method of the composite additive comprises the following steps: S1: ultrasonically dispersing titanium dioxide in dimethyl sulfoxide to form a dispersion, adding itaconic acid and an esterification catalyst to the dispersion, raising the system temperature to 100-110°C under stirring, keeping the temperature for 5-9 hours, allowing the material to cool naturally, separating the solid material by centrifugation, washing the solid material, and vacuum drying to obtain modified titanium dioxide; S2: Add modified titanium dioxide to N,N-dimethylformamide, ultrasonically disperse for 20 to 40 minutes, then add antifouling modification components and p-toluenesulfonic acid, raise the system temperature to 100 to 110°C, keep stirring for 6 to 10 hours, filter and separate the solid material, wash and dry it, and obtain a composite additive.

3. The method for preparing an anti-ultraviolet coating for glass surface according to claim 2, characterized in that: In step S1, the average particle size of the titanium dioxide is 5 μm.

4. The method for preparing an anti-ultraviolet coating for glass surface according to claim 2, characterized in that: In step S1, the esterification catalyst is any one of p-toluenesulfonic acid, aminosulfonic acid or trifluoromethanesulfonic acid.

5. The method for preparing an anti-ultraviolet coating for glass surface according to claim 2, characterized in that: In step S1, the mass ratio of titanium dioxide to itaconic acid is 1:0.1-0.

3.

6. The method for preparing an anti-ultraviolet coating for glass surface according to claim 2, characterized in that: The preparation method of the antifouling modified component comprises the following steps: The terminal hydroxyl fluorinated polysiloxane is mixed with dimethyl sulfoxide, stirred to form a uniform solution, and then the epoxy soybean oil and the phase transfer catalyst are added to the solution. After the addition is completed, the temperature is increased to 70-80°C, stirred at this temperature for 4-8 hours, and the solvent is removed by reduced pressure distillation to obtain an antifouling modified component.

7. The method for preparing an anti-ultraviolet coating for glass surface according to claim 6, characterized in that: The phase transfer catalyst is boron trifluoride ether complex.

8. The method for preparing an anti-ultraviolet coating for glass surface according to claim 6, characterized in that: The mass ratio of the terminal hydroxyl fluorinated polysiloxane to the epoxy soybean oil is 1:0.2-0.

4.

9. The method for preparing an anti-ultraviolet coating for glass surface according to claim 1, characterized in that: The initiator is any one of azobisisobutyronitrile, azobiscyclohexylmethane or azobisisovaleronitrile.

10. An anti-ultraviolet coating for glass surface, characterized in that: The method is as claimed in claim 1.

Citation Information

Patent Citations

  • A roof waterproof coating and its preparation method

    CN111171662B

  • Ultraviolet-curable fluorosilicone polyacrylate antifouling coating for glass and preparation method thereof

    CN113122101A

  • Water-phase instant titanium dioxide material as well as preparation method and application thereof

    CN114410131A

  • Thermal insulation coating for building glass and preparation method of thermal insulation coating

    CN118325416A